Empirical investigation of the theory of production function, with the data of alloy production in Ukraine - Matsuki, Y.; Bidyuk, P.; Kozyrev, V. (Системні дослідження та інформаційні технології, 2014)
In this research, a mathematical form of production function is investigated, which is a concept of microeconomics theory, with the actual data from the factory in Dnepropetrovsk Region of Ukraine, which produces the alloys from several input materials. A linear form of the production function was selected as the model, which consists of the variables that represent input materials together with their weighting factors, then the Lagrangean multiplier technique was used to transform this model in order to find the conditions for maximizing the output of the production, under a given cost constraint. The obtained conditions present the mathematical relations between the prices and the quantities of the input materials, which include unknown weighting factors. In order to get the values of the weighting factors, statistical analysis is made with the actual data. The result shows statistical significance of the model, therefore it is concluded that the selected linear function can be the production function. Проаналізовано математичну форму виробничої функції, яка є концепцією мікроекономічної теорії, з використанням фактичних даних, отриманих від підприємства в Дніпропетровській області України, яке виробляє сплави з декількох вхідних матеріалів. Лінійну форму виробничої функції було обрано в якості моделі, яка включає змінні, що представляють потоки вхідних матеріалів разом із своїми ваговими коефіцієнтами. Для розв’язання оптимізаційної задачі потім було застосовано метод множників Лагранжа для трансформації цієї моделі з метою визначення умови для максимізації об’єму вихідної продукції при обмеженні на видатки. Отримані умови представляють математичні співвідношення між ціною та об’ємом вхідних матеріалів, у тому числі невідомих вагових коефіцієнтів. Для того, щоб отримати значення вагових коефіцієнтів, виконано статистичний аналіз наявних фактичних даних. Отриманий результат свідчить про статистичну значущість моделі, а тому можна зробити висновок, що обрана лінійна функція може бути виробничою функцією. Проанализирована математическая форма производственной функции, которая является концепцией микроэкономической теории, с использованием фактических данных от предприятия в Днепропетровской области Украины, которые производит сплавы из нескольких входящих материалов. Линейная форма производственной функции была выбрана в качестве модели, состоящей из переменных, представляющих входящие материалы вместе со своими весовыми коэффициентами. Для решения оптимизационной задачи затем был применен метод множителей Лагранжа для трансформации этой модели с целью определения условий для максимизации объема выходной продукции при ограничениях на ресурсы. Полученные условия представляют математические соотношения между ценой и количеством входящих материалов, в том числе неизвестных весовых факторов. Для того, чтобы получить значения весовых коэффициентов, выполнен статистический анализ имеющихся фактических данных. Полученный результат свидетельствует о статистической значимости модели, поэтому можно сделать вывод, что выбранная линейная функция может быть производственной функцией.